Stellettin B Isolated from Stelletta Sp. Reduces Migration and Invasion of Hepatocellular Carcinoma Cells through Reducing Activation of the MAPKs and FAK/PI3K/AKT/mTOR Signaling Pathways. (29th November 2022) - Tsai, Tsung-Chang; Wu, Wen-Tung; Lin, Jen-Jie; Su, Jui-Hsin; Wu, Yu-Jen
Abstract : Hepatocellular carcinoma (HCC) is one of the most common malignant tumors, and there is currently a lack of effective treatment options to control the metastasis. This study was performed to examine the mechanisms of the migration and invasion characteristics of HCC, with the aim of reducing metastasis by inhibiting cancer cell migration and invasion. In this study, we used Stellettin B, an active compound isolated from Stelletta sponges, as the experimental drug and evaluated its inhibition effects on cell migration and invasion in human hepatoma cells (HA22T and HepG2). MTT assay, gelatin zymography, and western blotting were employed. The results showed that Stellettin B significantly inhibited the protein expressions of MMP-2, MMP-9, and uPA, while upregulating the protein expressions of TIMP-1 and TIMP-2. The expressions of p-FAK, p-PI3K, p-AKT, p-mTOR, and MAPKs (p-JNK, p-JUN, p-MAPKp38, and p-ERK) were decreased with increasing concentrations of Stellettin B. Our results suggest that Stellettin B-dependent downregulation of MMP-2 and MMP-9 activities could be mediated by FAK/PI3K/AKT/mTOR and MAPKs signaling pathways in HA22T and HepG2 cells, preventing HCC invasion and migration.